PELAYANAN PRIMA (SERVICE EXCELLENCE) DI PT. DAANISH MIKHA SALSA (DMS TOUR DAN TRAVEL LAMPUNG) - Vicky F. Sanjaya; Agil Nauval Ardiansyah (LPPM STAI DARUSSALAM LAMPUNG, 2021)
ABSTRAK Agil Nauval Ardiansyah, 2021, Excellent Service (Service Excellence) At PT. Daanish Mikha Salsa (DMS Tour and Travel Lampung) The focus of the problems studied in this study are: How is the concept of Excellent Service (Service Excellence) at PT. Daanish Mikha Salsa (DMS Tour and Travel Lampung). This study aims to determine and describe how the concept of Excellent Service (Service Excellence) at PT. Daanish Mikha Salsa (DMS Tour and Travel Lampung). Qualitative data obtained from documentation, interviews, and observations. Data analysis was carried out when and after collecting data. By using descriptive, data analysis is done by reduction, display, conclusion drawing/verification. This study found that there is Excellent Service (Service Excellence) at PT. Daanish Mikha Salsa (DMS Tour and Travel Lampung) is the existence of excellent service when pilgrims come and are greeted by greeting, providing hospitality in serving, and smiling. Barrier factors in the application or implementation of service excellence (service excellence) at PT. Daanish Mikha Salsa (DMS Tour and Travel Lampung) are: HR officers at the time of handling are very limited, documentation is inadequate and maximal and there is a lack of APS equipment (audio during Thawaf and Sa'i). As the concept of Excellent Service which supports the overall service, starting from administrative registration, rituals, to the departure and return of pilgrims. Keywords: Concept of Excellent Service (Service Excellence), Barrier Factors ABSTRAK Agil Nauval Ardiansyah, 2021, Pelayanan Prima (Service Excellence) Di PT. Daanish Mikha Salsa (DMS Tour dan Travel lampung) Fokus masalah yang diteliti dalam penelitian ini adalah: Bagaimana konsep Pelayanan Prima (Service Excellence) di PT. Daanish Mikha Salsa (DMS Tour dan Travel lampung). Penelitian ini bertujuan untuk mengetahui dan mendeskripsikan Bagaimana konsep Pelayanan Prima (Service Excellence) di PT. Daanish Mikha Salsa (DMS Tour dan Travel lampung). Data kualitatif diperoleh dari dokumentasi, wawancara, dan observasi. Analisis data dilakukan ketika dan setelah mengumpulkan data. Dengan menggunakan deskriptif, analisis data dilakukan reduction, display, conclution drawing/verification. Penelitian ini menemukan bahwa terdapat Pelayanan Prima (Service Excellence) di PT. Daanish Mikha Salsa (DMS Tour dan Travel lampung) adalah adanya pelayanan prima pada saat jamaah datang disambut dengan mengucapkan salam, memberikan keramahan dalam melayani, dan murah senyum. Faktor-faktor hambatan dalam penerapan atau implementasi pelayanan prima (service excellence) di PT. Daanish Mikha Salsa (DMS Tour dan Travel lampung) adalah : petugas SDM pada saat handling sangat terbatas, dokumentasi kurang memadai dan maksimal dan minimnya alat APS (audio saat Thawaf dan Sa’i). Sebagaimana konsep Pelayanan Prima yang mendukung dalam pelayanan keseluruhan mulai dari pendaftaran administrasi, manasik, hingga keberangkatan dan kepulangan jamaah. Kata kunci : Konsep Pelayanan Prima (Service Excellence), Faktor-Faktor Hambatan